UPAYA REDUKSI SEARCHING TIME DENGAN METODE 5S PADA AREA GUDANG PENYIMPANAN BARANG DI PT URF - Sri Wardani; Intan Bunga Kharisma; Yoga Rochmutiarawan Nurazis (Universitas Widyatama, 2021)
PT URF is a procurement and service company engaged in the refrigeration sector, especially in the field of refrigeration integrated building construction. In carrying out its procurement, PT URF has a warehouse as a storage area for goods which is an important component and makes an important contribution to the speed of a project work. However, currently the company still uses conventional methods in its storage system. So that in its repair efforts, the company plans to improve the arrangement, sorting, cleaning and maintenance of goods in the warehouse area using one of the lean tools, namely the 5S concept, which aims to reduce the searching time for inventory in the warehouse area. The results of the design carried out are rearranging the placement of goods or materials, cleaning, and implementing procedures in accordance with the 5S concept.